Influence of probionts on the gut microbial diversity in pearl spot, Etroplus suratensis (Bloch) - Immanuel, G; Menenthira, V; Prema, P; Palavesam, A (Indian Journal of Fisheries, 2011)
Qualitative and quantitative aspects of bacterial population in the gut of Etroplus suratensis collected from wild, following one day starvation and also in fishes fed with probionts supplemented diets such as Lactobacillus acidophilus (Feed A) and Yeast - Saccharomyces cervisiae (Feed B) were studied. The total aerobic heterotrophic bacterial counts in gut contents of wild and one day starved fish were 31.0 x 106 and 22.6 x 106 CFU / ml. Similarly in fishes fed with probionts supplemented diets and control diet (Feed C) cultured for 15 and 30 days, the bacterial counts registered were 26.40 x 106, 22.9 x 106 and 29.9x 106 CFU / ml and 28.2x 106, 27.6x 106 and 22.3 x 106 CFU/ml during 15th and 30th days of experiment in fish fed with L. acidophilus, Yeast, S. cervisiae and control diets respectively. Totally eleven bacterial genera were identified in all the gut samples and among these, Pseudomonas, Bacillus, Micrococcus and Alcaligenes were dominant during 30th day of the experiment.